EXPLORING CULTURAL, POLITICAL, AND SOCIOECONOMIC INFLUENCES ON COLLECTIVE PSYCHOLOGICAL RESILIENCE IN LIBYA - Abrahem Masuwd, Mowafg; Baroud, Najah (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2025)
This study explores the factors that shape collective psychological resilience in Libya, particularly in the context of the nation’s recent political instability, economic challenges, and complex cultural dynamics. The paper examines how these elements interact to strengthen or undermine community resilience, using a mixed-methods approach. Through qualitative interviews and quantitative data analysis, this research identifies key determinants of psychological resilience, focusing on cultural values, social capital, and economic conditions in Libyan society. Political instability, compounded by a decade of conflict, has forced communities to adapt and develop unique forms of resilience. This study also delves into the role of familial and community structures in coping with adversity, as well as the impact of government policies and foreign influence on the collective psyche of Libyan citizens. The findings suggest that while political and socioeconomic factors have undeniably shaped resilience, cultural influences rooted in communal solidarity and the importance of social support networks have played a central role in fostering psychological resilience. Understanding these complex factors is crucial for designing interventions aimed at improving mental health and social stability in post-conflict societies. The paper concludes with recommendations for policy makers and international organizations seeking to enhance psychological resilience through culturally appropriate and context-sensitive strategies.